Alternatives to ability grouping students for reading instruction in the elementary school - Amann, Teresa A. (My University, 1992)
How to group students effectively for reading instruction in the elementary school is a decision every teacher or every school district must make. The purpose of this paper was to review literature on ability grouping elementary students for reading instruction and to present current research on alternatives to ability grouping. Four specific alternatives were addressed in this paper: cooperative learning, mastery learning, peer tutoring, and flexible grouping. The paper also presented strategies for applying these alternatives in the elementary classroom.
Keywords: Group work in education; Reading (Elementary); Ability grouping in education